Acoustic emission monitoring of a mechanochemical surface finishing process. (August 2017) - Strömbergsson, Daniel; Marklund, Pär; Edin, Emil; Zeman, Frida
Abstract: Acoustic emission monitoring of cutting machining operations is an established researched area, though monitoring non-removal finishing processes is less studied. This work presents an initial investigation on Acoustic emissions potential of an mechanochemical superfinishing process. Conclusions are drawn from the monitoring signal regarding the resulting surface friction characteristics, composition and possible runnability issues. Monitoring data was collected from tests performed at Applied Nano Surfaces' testing laboratory. Test series with varying parameters enabled a correlation analysis between the monitoring data, surface friction characteristics and tribofilm formation. Increasing tool wear tests were monitored to find early runnability warning. Results shows Acoustic emissions indication potential when the finishing process has achieved the intended friction reduction, tribofilm deposition as well as runnability issues identification.